Optimalisasi Pelayanan Distribusi Obat Premedikasi Pasien Onkologi Di Ruang Perawatan Kemoterapi: Optimizing Patient Premedication Drug Distribution Services Oncology In The Chemotherapy Treatment Room - Ambarika, Rahmania; Rahmi, Dianita (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Ineffective communication between pharmacy staff and nurses during the handover process of premedication drugs at the Oncology Pharmacy Depot of RSUD Provinsi NTB often causes discomfort for patients and their families. This issue impacts the efficiency of drug distribution services, requiring strategic solutions. This study aims to analyze the factors contributing to the suboptimal distribution of premedication drugs, develop Standard Operating Procedures (SOPs), and devise strategies to improve the quality of drug distribution services for chemotherapy patients. Methodology: The approach used was a SWOT analysis to evaluate strengths, weaknesses, opportunities, and threats in premedication drug distribution services. The WO (Weakness-Opportunity) strategy was selected to address internal weaknesses by utilizing external opportunities, such as implementing socialization programs and strengthening monitoring and evaluation efforts. The development of SOPs related to premedication drug distribution, the creation of a premedication drug handover logbook, and the implementation of socialization programs for pharmacy staff and nurses have significantly improved coordination among personnel. These measures contributed to a reduction in patient complaints regarding delays in drug distribution and enhanced service efficiency. The implementation of SOPs, a handover logbook, and socialization programs are effective steps in improving the quality of premedication drug distribution services in oncology wards. This intervention is expected to serve as a model for application in other pharmacy installations to enhance the quality of pharmacy services.